Ultrasonic Disintegration Effects on Excess Sludge with Different-Sized Ultrasonic Probes - Atay, Seyma; Akbal, Feryal; Ozbey, Mustafa (Wiley, 2025)
Ultrasonic disintegration based on lysis-cryptic growth improves sludge characteristics. Many factors affect ultrasonic disintegration of the excess sludge. This study aimed to provide better insight into ultrasonic disintegration effects on excess sludge at different energy levels, probes, and times. The results demonstrated that ultrasonic disintegration with 13 and 25 mm probes released significant amounts of chemical oxygen, and the degree of disintegration (DDCOD) significantly (p < 0.001) increased with specific energy (E-S) input. The results indicated that the total coliform (TC), fecal coliform (FC), and Escherichia coli (EC) counts increased at lower energy levels and decreased at higher energy levels. Consequently, bacterial inactivation significantly (p < 0.001) increased. According to the EPA 40 CFR 503 regulation, ultrasonic disintegration based on lysis-cryptic growth produces Class B biosolid and can be recommended as a process to reduce pathogens. This study examined that the tip diameter of the probe is an important parameter for ultrasonic disintegration. At the same sonication time and amplitude, probes with smaller tip diameters produced greater cavitation density, whereas probes with larger tip diameters produced less cavitation intensity. Additionally, probes with larger tip diameters were less costly at higher ES levels so that they could be integrated into full-scale applications at higher E-S levels.
Keywords: Cost Analysis; Excess Sludge; Lysis-Cryptic Growth; Specific Energy (E-S); Ultrasonic Disintegration